Fatty acid chain length impacts nanonizing capacity of albumin-fatty acid nanomicelles: Enhanced physicochemical property and cellular delivery of poorly water-soluble drug - Park, Chulhun; Meghani, Nileshkumar; Loebenberg, Raimar; Cui, Jing Hao; Cao, Qing Ri; Lee, Beom Jin (European Journal of Pharmaceutics and Biopharmaceutics, 2020)
This study aimed to design the ideal nanonizing vehicle for poorly water-soluble model curcumin (CCM) using fattigation-platform nanotechnology, and to investigate the effects of fatty acid salts chain length on nanonizing CCM and its efficient delivery to different cancer cells. HSA-fatty acid conjugates were synthesized by EDC/NHS coupling. Fattigation-platform nanomicelles (NMs), prepared by film hydration, exhibited uniform and spherical morphology, although, each NM varied in particle size, zeta potential, and critical micelle concentration according to the types of fatty acid. Preliminary solubility studies of albumin conjugates with 5 types of fatty acid salts of different chain lengths revealed that C14 exhibited the highest solubilization of CCM. CCM-loaded HSA-C14 NMs demonstrated the highest drug content (5.35 ± 0.48%) and loading efficiency (95.93 ± 1.87%) compared to other NMs. It exhibited enhanced drug release rate and reduced micelle size in biorelevant dissolution medium. Interestingly, this solubilization approach was well applied in poorly water-soluble docetaxel trihydrate (DTX). Preliminary solubility results of DTX was also corresponded to the stable nanonization phenomenon in biorelevant dissolution medium. Compared to the CCM EtOH solution, HSA-C14 NMs showed higher internalization in cancer cell lines A549 and MCF-7, and consequently, exhibited significantly increased cytotoxicity against both cell lines. Therefore, this study provides a new solubilization approach for poorly water-soluble drugs using fatty acid salts of different chain lengths and their micellar formations via nanonization, which could be a promising tool for targeted cancer therapy using poorly water-soluble drugs.
Keywords: A549 Cells; Albumins; Cell Line; Cell Line, Tumor; Curcumin; Docetaxel; Drug Carriers; Drug Liberation; Fatty Acids; HEK293 Cells; Humans; MCF-7 Cells; Micelles; Nanoparticles; Nanotechnology; Particle Size; Solubility; Water; Cellular delivery; Cytotoxicity; Fatty acid chain length; Nanomicelles; Nanonization; Physicochemical property; Solubilization